(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper presents a comprehensive analysis of bank credit and loan waivers, examining their impacts on financial institutions, borrowers, and the broader economy. Loan waivers have been a contentious policy tool, often used to address financial distress among borrowers but raising concerns about moral hazard and systemic risks. Drawing on a review of existing literature, empirical evidence, and case studies, this paper evaluates the effectiveness and consequences of loan waiver programs. It explores the effects of loan waivers on bank profitability, credit availability, borrower behavior, and macroeconomic stability. Additionally, the paper identifies gaps in current research and proposes future directions for scholars and policymakers to further understand the dynamics of loan waivers in the banking sector. By shedding light on the complexities of bank credit and loan waivers, this research contributes to informed policy decisions and financial practices aimed at achieving sustainable and inclusive economic growth.